PERAN SERVANT LEADERSHIP, KEPERCAYAAN DAN BUDAYA ORGANISASI DALAM MEMPENGARUHI LOYALITAS ANGGOTA - kuswanto, kuswanto (Journal MISSY (Management and Business Strategy), 2025)
Members' loyalty to the organization is essential because it has a significant impact on the organization's long-term success and stability because loyal members tend to be more motivated and committed to working well, which can improve the productivity and efficiency of the organization. This study examines the role of servant leadership, trust, and organizational culture in influencing the loyalty of organizational members, with a sample of 127 from a population of 186 PGRI members in Kembangbahu District. A quantitative method was chosen in this study and data collection was carried out by distributing questionnaires in the form of statements and questions that were carefully designed to measure the variables of loyalty, servant leadership, trust and organizational culture. The results of the analysis show that Servant Leadership has a positive and significant impact on the results. Organizational culture has also been proven to have a significant and strong influence and a high level of significance. Meanwhile, Confidence, although showing a positive relationship with outcomes, is not statistically significant at conventional levels, indicating that its effect is weaker and less reliable compared to other variables.